Uncle of the year : & other debatable triumphs - Rannells, Andrew (Crown, an imprint of Random House, 2023)
"In Uncle of the Year, Andrew Rannells wonders: If he, now in his early forties, has everything he's supposed to need to be a true adult-a career, property, a well-tailored suit-why does he still feel like an anxious twenty-year-old climbing his way toward security? Is it because he hasn't won a Tony, or found a husband, or had a child? And what if he doesn't want those things? (A husband and a child, that is. He wants a Tony.) In essays drawn from his life and career, Rannells argues that we all pretend we are constantly winning. And with each success, we act like we've reached the pinnacle of happiness (for our parents), maturity (for our friends), success (for our bosses), and devotion (for our partners). But if "adulting" is just a pantomime that's leaving us unmoored, then we need new markers of time, new milestones, new expectations of what adulthood is-and can be. Along the way, Rannells looks back, reevaluating whether his triumphs were actually failures-and his failures, triumphs-and exploring what it will take to ever, ever feel like he has enough... Filled with witty and honest insights, and a sharp sense of humor, Uncle of the Year challenges us to take a long look at who we're pretending to be, who we know we are, and who we want to become"--